Pharmacophore generation of 2-substituted benzothiazoles as AdeABC efflux pump inhibitors in A. baumannii - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2014)
RND family efflux pumps are important for multidrug resistance in Gram-negative bacteria. To date no efflux pump inhibitors for clinical use have been found, so developing the specific inhibitors of this pump system will be beneficial for the treatment of infections caused by these multidrug-resistant pathogens. A set of BSN-coded 2-substituted benzothiazoles were tested alone and in combination with ciprofloxacin (CIP) against the RND family efflux pump AdeABC overexpressor Acinetobacter baumannii SbMox-2 strain. The results indicated that the BSN compounds did not have antimicrobial activity when tested alone. However, if they were applied in combination with CIP, it was observed that the antibiotic had antimicrobial activity against the tested pathogen, possessing a minimum inhibitory concentration value that could be utilized in clinical treatment. A 3D-common features pharmacophore model was applied by using the HipHop method and the generated pharmacophore hypothesis revealed that the hydrogen bond acceptor property of nitrogen in the thiazole ring and the oxygen of the amide substituted at the second position of the benzothiazole ring system were significant for binding to the target protein. Moreover, three hydrophobic aromatic features were found to be essential for inhibitory activity.
Keywords: benzothiazoles; A; baumannii SbMox-2; AdeABC; ciprofloxacin; HipHop; pharmacophore generation; RESISTANT ACINETOBACTER-BAUMANNII; IN-VITRO ACTIVITY; ANTIMICROBIAL RESISTANCE; CONFORMATIONAL COVERAGE; PSEUDOMONAS-AERUGINOSA; HOSPITALIZED-PATIENTS; MULTIDRUG-RESISTANCE; UNITED-STATES; SUSCEPTIBILITY; 1-(1-NAPHTHYLMETHYL)-PIPERAZINE